The Harmonization of Ecology and Balinese Local Identity through Music by Indie-Folk Trio Nosstress - Yuanita Albhar (Universitas Airlangga, 2019)
This study explores the importance of art and ecological values in Bali, especially during the reclamation of Tanjung Benoa nowadays, which is reflected in the existence of music by Indie-Folk Trio Nosstress. Those two prominent aspects interweave the other facets in Bali”nature, social, culture, economy, until spiritualism”which then makes the basic tenet of Tri Hita Karana becomes harmonious. Using qualitative method as well as the theory of Constructing Community initiated by Barbara Hatley, the results of this study show that the ‘reality' value of that phenomena is disharmonization between ecology and local which lies on the first half of the lyrics. Whereas the rest of the lyrics depict the need to revitalize the harmonization of both aspects which becomes the ‘ideal' value from those Balinese artists. In conclusion, this study denotes that the ecological disharmony, that still strucks Bali until these days, is considered as a heavy polemic. This is because the role of nature as one of the aspects of basic principle Tri Hita Karana, makes it become respected as an essential thing for the Balinese society itself.